Performance of OCDMA systems using a complementary subtraction technique - Hasoon, Feras N.; Mohamad Khazani, Abdullah; Syed Alwee Aljunid, Syed Junid; Sahbudin, Shaari (Optical Society of America, 2009)
Link to publisher's homepage at http://www.osa.org/